Prenatal diagnosis and molecular cytogenetic characterization of a de novo deletion of 4q34.1→qter associated with low PAPP-A and low PlGF in the first-trimester maternal serum screening, congenital heart defect on fetal ultrasound and a false negative non-invasive prenatal testing (NIPT) result - Chih-Ping Chen; Shin-Wen Chen; Liang-Kai Wang; Schu-Rern Chern; Peih-Shan Wu; Fang-Tzu Wu; Li-Feng Chen; Wayseen Wang (Elsevier, 2022)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a de novo deletion of 4q34.1→qter associated with low pregnancy associated plasma protein-A (PAPP-A) and low placental growth factor (PlGF) in the first-trimester maternal serum screening, congenital heart defect (CHD) on fetal ultrasound and a false negative non-invasive prenatal testing (NIPT) result. Case Report: A 40-year-old, primigravid woman underwent amniocentesis at 20 weeks of gestation because of advanced maternal age. This pregnancy was conceived by in vitro fertilization (IVF) and embryo transfer (ET). First-trimester maternal serum screening at 12 weeks of gestation revealed low PAPP-A [0.349 multiples of the median (MoM)] and low PlGF (0.299 MoM) and showed a risk for fetal trisomy 21 and trisomy 13. However, NIPT detected no genomic imbalance and a normal result. Nevertheless, level II ultrasound revealed ventricular septal defect, single umbilical artery and a small brain midline cyst. Amniocentesis revealed a karyotype of 46,XX,del(4)(q34.1) and a 17.8-Mb deletion of 4q34.1q.35.2 on array comparative genomic hybridization (aCGH) analysis. The parental karyotypes were normal. The pregnancy was terminated at 23 weeks of gestation, and a malformed fetus was delivered with craniofacial dysmorphism. Postnatal cytogenetic analysis of the placenta confirmed the prenatal diagnosis. There was a 17.8-Mb deletion of 4q34.1q.35.2 encompassing the genes of HAND2, SORBS2 and DUX4. Polymorphic DNA marker analysis on the parental bloods and cord blood showed a paternal origin of the deletion. Conclusion: An abnormal first-trimester maternal serum screening result along with abnormal fetal ultrasound should alert the possibility of fetal aneuploidy, and amniocentesis is indicated even in the presence of a normal NIPT result.